Professional environment and patient safety in emergency departments - Lambrou, Persefoni; Papastavrou, Evridiki; Merkouris, Anastasios; Middleton, Nicos (My University, 2015)
Abstract The purpose of this study was to examine nurses' and physicians' perceptions of professional environment and its association with patient safety in public emergency departments in Cyprus. A total of 224 professionals (174 nurses and 50 physicians) participated (rr = 81%). Data were collected using the "Revised Professional Practice Environment" (RPPE) instrument and the Safety Climate Domain of the "Emergency Medical Services Safety Attitudes Questionnaire" (EMS-SAQ). The mean overall score of RPPE was 2.79 (SD = 0.30), among physicians 2.84 (SD = 0.25) and nurses 2.73 (SD = 0.33) (P-value = 0.07). Statistically significant differences were observed between the two study groups regarding "staff relationships", "motivation" and "cultural sensitivity" (P-values < 0.05). No significant differences were observed as regards EMS-SAQ (3.25 vs. 3.16 respectively; P-value = 0.28). All 8 components of the RPPE exhibited significant association with patient safety. Linear and stepwise regression analyses showed that "leadership" explains 28% of the variance of safety. This relationship suggests improvements in professional environment with the ultimate goal of improving patient safety.
Keywords: Emergency department; Nurse; Patient safety; Physician; Professional environment